Watershed Distributed Hydrological Modeling With Gis-Tools - Kostrikov, S. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
The paper introduces both methodological principles and applied software implementation of watershed distributed hydrological modeling.  Several various definitions of a distributed model are emphasized. The algorithmic calculation of the initial basin area is considered in details upon hydrological flow simulation on the digital elevation model matrix. There are several examples of  author’s  software hydrological graphic user’s interface in this paper. These examples relate to the channel extreme flow discharge modeling upon spring flood. A direct such modeling is introduced with all its steps.